Research on Spatiotemporal Characteristics of College Students' Health Information Search in Public Health Emergencies - Chen Jing (LIS Press, 2021)
[Purpose/significance] This research explores the relationship between the health information search behaviors of college students and the spatiotemporal situation of public health emergencies, in order to reveal the coupling characteristics of users' health information search behaviors and public health emergencies. [Method/process] Using mobile experience sampling method and key event method to collect 380 college students’ health information search diary data as research samples, the process of user information search (information sources selection, information search patterns) and results (information utilization methods, health awareness and emotional perception) in public health emergencies were the entry points, and spatiotemporal characteristics of health information search in the context of public health events of college students were statistically analyzed. [Result/conclusion] The spatiotemporal coupling characteristics of user health information search results of college students in public health emergencies are obvious. The combined using way of health information search and changes in health consciousness of college students both show significant differences in time and space distribution. In the outbreak period and high-risk areas, users prefer to sharing information offline while self-use, and the level of health awareness changes is relatively high. In the duration period and low and medium risk areas, users prefer to share online while self-use, and the level of health awareness changes is relatively low. Although the single using way of information and emotional perception do not show significant differences in time and space distribution, the single using way of information spatiotemporal coupling characteristics are still reflected in descriptive data. The search process of college students' health information shows normalized features such as users' habitual use of mobile devices as information sources and preference information encounters. This research reveals the spatiotemporal contextual characteristics of health information search behaviors in emergencies, which helps the information service department in-depth grasp the law of information behavior changes in different periods and regions of public health emergencies and improve accurate information services level.